Knowledge about Cryptocurrencies: Consumer Behavior Survey - xenia scimone (International Journal of Community Service & Engagement, 2022)
Although the cryptocurrency market has grown significantly in recent years, few studies have been done on socio-demographic features and not influencing the degree of consumer knowledge about cryptocurrencies. Based on a survey submitted to 774 subjects representative of the Italian population, we find that 89% of Italians know cryptocurrencies and 39% of them have a good or thorough knowledge. The aptitude for knowledge and use of cryptocurrencies is greater for male and well-educated subjects and also increases as the propensity to invest in cryptocurrencies increases. 41% invest or want to invest in cryptocurrencies and the investment is particularly attractive for those who mainly aim at portfolio diversification and obtaining high returns. The findings have important implications for regulators and supervisors who are interested in understanding the social relevance of the phenomenon.